Retroperitoneal ganglioneuroma a case report - Oyama, N (Hinyokika kiyo. Acta urologica Japonica, 1996)
We experienced a case of ganglioneuroma. A 37-year-old man was admitted to our hospital for right flank pain. Computed tomography (CT) showed a low density mass near the upper pole of the right kidney. Selective renal arteriography did not demonstrate any tumor vessels in the right kidney. An endocrinological study revealed high values of noradrenaline and dopamine in urine. Under the preoperative diagnosis of a retroperitoneal tumor or right adrenal tumor, tumor resection was performed. The tumor was found in the retroperitoneal space on surgical exploration. The histopathological diagnosis was ganglioneuroma